Scaffolding and Vignette-Based Learning Strategy to Support Student Attention in Linear Regression - Agustin, Dhabitah Mulya; Damayanti, Nia Wahyu (Jurnal Likhitaprajna, 2026)
Students with attention difficulties often experience challenges in maintaining focus and sustaining engagement during mathematics learning. This study aimed to examine the implementation of scaffolding integrated with vignette-based learning in supporting student attention during linear regression instruction. This study employed a Single Subject Research (SSR) design using an A–B format, consisting of a baseline phase and an intervention phase. The research subject was one eleventh-grade student from a vocational high school who was selected using purposive sampling based on preliminary observation and teacher information indicating attention difficulties during mathematics learning. Data were collected through structured observation using 30-second interval recording, focusing on four attention indicators: latency, on-task behavior, prompting frequency, and distraction frequency. The data were analyzed using visual analysis to identify changes in level, trend, and variability across sessions. The results showed an increase in on-task behavior and a decrease in prompting frequency, indicating improved engagement and reduced reliance on external assistance. Distraction also decreased, although latency remained variable. The findings suggest that scaffolding integrated with vignette-based learning can support sustained attention and engagement through structured assistance and contextualized instruction. However, attention improvement was not entirely stable, particularly in task initiation.